Physical map of the centromeric region of human chromosome 7: relationship between two distinct alpha satellite arrays. - Wevrick, R (1991)
A long-range physical map of the centromeric region of human chromosome 7 has been constructed in order to define the region containing sequences with potential involvement in centromere function. The map is centered around alpha satellite DNA, a family of tandemly repeated DNA forming arrays of hundreds to thousands of kilobasepairs at the primary constriction of every human chromosome. Two distinct alpha satellite arrays (the loci D7Z1 and D7Z2) have previously been localized to chromosome 7. Detailed one- and two- locus maps of the chromosome 7 centromere have been constructed. Our data indicate that D7Z1 and D7Z2 arrays are not interspersed with each other but are both present on a common Mlu I restriction fragment estimated to be 3500 kb and 5500 kb on two different chromosome 7's investigated. These long-range maps, combined with previous measurements of the D7Z1 and D7Z2 array lengths, are used to construct a consensus map of the centromere of chromosome 7. The analysis used to construct the map provides, by extension, a framework for analysis of the structure of DNA in the centromeric regions of other human and mammalian chromosomes.